Analisis finansial pada usaha budidaya rumput laut Kappaphycus alvarezii di Desa Akle, Kecamatan Semau Selatan, Kabupaten Kupang - Lilong, Syuni Y; Sunadji, Sunadji; Ratoe Oedjoe, Marcelien Dj (Nusa Cendana University, 2024)
Kappaphycus alvarezii, a type of red algae from the Rhodophyta group, produces carrageenan which has various important uses in the food industry, pharmaceuticals, cosmetics and other sectors. The global demand for carrageenan makes it a commodity that is in demand on the international market. This research aims to identify the characteristics of K. alvarezii seaweed cultivators, carry out financial analysis, and identify the obstacles faced and how to overcome them in the cultivation business. The research results show that the majority of cultivators in Akle Village have cultivation experience of around 11-19 years (48%), low education (31% have not completed elementary school), age range between 20-60 years (87.5 %), and the number of family dependents is 4 people (25%). The seaweed cultivation business in Akle Village, South Semau District, Kupang Regency is considered feasible to continue based on Break Even Point (BEP) and Benefit Cost Ratio (BC) analysis. The obstacles faced include disturbances from turtles, fish and ice-ice disease, which can be overcome by making fences from trawls and using superior seeds. Keywords: Financial analysis, Kappaphycus alvarezii, respondent characteristics, constraints, seaweed.